STRATEGI PENGEMBANGAN INDUSTRI KECIL BATAKO DI KOTA PEKANBARU - Hapsari Ayu Firdha; Iyan Yani Rita; Mardiana Mardiana (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2020)
This research aims to know the strategy of small business development of brick in the future. The population is a total of 6 businesses with census methods. Variables in the research are raw materials, marketing, human resources and technology. Technical analysis of the data used is using SWOT analysis. In the results of the study showed small brick industry in Pekanbaru City is in the position of SWOT Matrix Quadrant 1 which means the right strategy for the brick industry in Pekanbaru City is a strategy to grow and build (Growth and Build) to produce the most precise strategy then further analyzed by using internal matrix and external matrix and the result of small brick industry in Pekanbaru City is in the intermediate position in cell 5 namely growth and stability so that the right strategy is the development of Product market and market penetration.Keywords: strategy, SWOT analysis, brick industry.